Impact of narcissistic personality disorder on cognitive organizational cynicism with mediating role of psychological capital in selected hospitals of Punjab Pakistan - Irfan Sabir; Shahbaz Hussain; Muhammad Bilal Majid; Asad-ur Rehman; Arslan Sarwar; Farooq Nawaz (Future Business Journal, 2020)
Purpose: The purpose of this research work was to analyze the narcissism personality disorder in nurses and their impact on cognitive organizational cynicism with mediating role of psychological capital. Design/methodology/approach: In the current study, constructs developed from existing theories, generate hypotheses, adopt strategies for data collection and perform test to prove the proposed hypothesis. The nursing carder is the unit of analysis in this research study. Descriptive statistics, correction, and mediation analysis through Baron and Kenny's were performed for analysis. Findings: This research concludes narcissism personality disorder has significant positive association with cognitive organizational cynicism. The role of psychological capital is mediating to minimize the negative employee's behavior toward their bosses and organization. Practical implications: In the light of findings, the current research work has implications at individual and organization levels. This research work will become as foundation stone to formulate strategies to overcome the organization cynicism in nursing profession. Furthermore, the organization formulates selection process more affective to find those candidates having narcissism disorder. Originality/value: The current research work is designated first study to evaluate the relationship between narcissistic personality disorder and cognitive organization cynicism with mediating role of psychological capital in Pakistan.
Keywords: 650; Narcissistic personality disorder; Cognitive organizational cynicism; Psychological capital and hospitals of Punjab Pakistan